Outside Front Cover: Plasma Process. Polym. 8/2022. Issue 8 (4th August 2022) - Jung, Unseok; Kim, Hyun Su; Jeong, Hyeon Su; Suhr, Jonghwan; Kim, Tae‐Hwan; Lee, Hunsu
Abstract : Outside Front Cover : In plasma functionalization, it is confirmed that radicals penetrate from bulk plasma into the deepest layer of CNTs to functionalize the entirety of CNTs. The radical penetration is hindered as the thickness of CNTs increases, but when the porosity increase, the thickness effect is offset in spite of thickness of CNTs increases, which leads to a radical penetration into the deepest layer of entire CNTs. These experimental results are consistent with the calculated results by radical penetration model. Further details can be found in the article by Unseok Jung, Hyun Su Kim, Hyeon Su Jeong, Jonghwan Suhr, Tae‐Hwan Kim, and Hunsu Lee (e2200010 )